An Implementation of Fuzzy PD Control Design for Five Flip Folders Folding Machine Using Arduino Mega2560 - wahyu setyo pambudi; Efrita Arfah Zuliari; Riza Agung Firmansyah; Muhammad Hasbi Nasiruddin (Universitas Dharma Wacana, 2020)
The arm manipulator application that has 1 degree of freedom (DOF) can be used to flip folders in folding machines. The used actuator in folding machine is a Brushed DC motor. The Fuzzy-PD control system in this application is using Arduino Mega2560 microcontroller. Application of Fuzzy-PD control system on folding machine is able to move 5 flip folders. This Fuzzy-PD control system is able to improve the system response when there is a load, where the difference is only 7.73% from the no load condition. In addition, to implement this flip folder, a stochastic based method (ARX) is also applied on this system so it can be simulated directly. The simulation results from this folding machine model have a time constant of 0.510s, rise time of 1.501s, settling time of 1.5320s and delay time of 0.353s.